Perilaku Pencegahan dan Risiko Kejadian Diabetes Melitus Tipe 2 pada Usia Produktif di Kabupaten Bogor Tahun 2021: Prevention Behavior and Risk of Type 2 Diabetes Mellitus in the Productive Age in Bogor Regency in 2021 - Maspupah, Tari; Nina; Siagian, Trinita Debora; Pakhpahan, Judika; Octavianie, Gina (Journal of Public Health Education, 2022)
Background: The International Diabetes Federation (IDF) predicts an increase in the number of diabetes patients in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. Based on various epidemiological studies, type 2 diabetes mellitus constitutes more than 90% of the entire diabetic population. There are two risk factors that can lead to Type 2 Diabetes Mellitus: genetic factors and behavioral factors (physical activity, healthy eating patterns, smoking behavior, alcohol consumption, and regular health check-ups). Objective: To understand the prevention behavior and risk of Type 2 diabetes mellitus incidents in the productive age group in the Bogor regency in 2021. Method: This research was conducted from January 3rd to February 3rd, 2022, using a quantitative method. The research took place in Bogor Regency, West Java. The population in this study was the entire community of Bogor Regency, with a sample size of 447 people. The instrument used was a questionnaire distributed online through Google Forms. Results: The research indicates that 8.1% have a genetic risk of diabetes mellitus, the influencing factor in smoking remains high at 76%, and the low number of people undergoing regular health check-ups is only 14.7%. Prevention efforts are made by educating on the importance of early prevention of diabetes mellitus by starting to adopt a healthier lifestyle, implementing the "Gerakan Masyarakat Sehat" (Healthy Community Movement) behavior to avoid the risk of diabetes mellitus. Conclusion: There are two risk factors causing diabetes mellitus in the Bogor regency: genetic factors and GERMAS behavior (physical activity, healthy eating patterns, smoking behavior, alcohol consumption, and regular health check-ups).